2010
DOI: 10.1002/ijc.24764
|View full text |Cite
|
Sign up to set email alerts
|

Down‐regulation of BiP/GRP78 sensitizes resistant prostate cancer cells to gene‐therapeutic overexpression of REIC/Dkk‐3

Abstract: We have recently shown that an adenovirus carrying REIC/Dkk‐3 (Ad‐REIC) exhibits a potent tumor‐specific cell‐killing function for various human cancers. It has also become evident that some human cancers are resistant to Ad‐REIC‐induced apoptosis. The aim of the present study was to determine the molecular mechanisms of resistance to Ad‐REIC. First, we isolated resistant clones from a human prostate cancer cell line, PC3, after repeated exposure to Ad‐REIC. Infection efficiency of the adenovirus vector and ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 22 publications
(31 reference statements)
1
12
0
Order By: Relevance
“…The glucose-regulated protein, Hspa5, belongs to the Hsp70 protein family, which is involved in a number of cellular processes that maintain the homeostasis of cells. It is strongly induced in tumors and plays critical roles in the stress of oncogenesis (15)(16)(17)(18). We previously showed that the overexpression of Hsp70-2 protected cancer cells against apoptosis induced by hypoxia and that the upregulated expression of Hspa5 protected NIT-1 cells from death induced by streptozotocin, cytokines or cytotoxic T lymphocytes (19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…The glucose-regulated protein, Hspa5, belongs to the Hsp70 protein family, which is involved in a number of cellular processes that maintain the homeostasis of cells. It is strongly induced in tumors and plays critical roles in the stress of oncogenesis (15)(16)(17)(18). We previously showed that the overexpression of Hsp70-2 protected cancer cells against apoptosis induced by hypoxia and that the upregulated expression of Hspa5 protected NIT-1 cells from death induced by streptozotocin, cytokines or cytotoxic T lymphocytes (19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…A study utilizing the gastrocnemius muscle of mdx and wild‐type mice found elevated levels of stress‐related chaperone proteins such as GRP78 . This is potentially a very interesting finding as GRP78 (also known as BiP) levels have already been altered as therapeutic intervention in other diseases such as cancer and photoreceptor degeneration . In this study, around 9.3% of 789 detected proteins were significantly altered.…”
Section: Resultsmentioning
confidence: 53%
“…We also reported that resistant clones isolated from sesitive PC3 prostate cancer cells expressed BiP/Grp78, an ER-resisting chaperone protein, at enhanced levels (20). Downregulation of BiP/Grp78 with specific siRNA sensitized the resistant clones to Ad-REIC.…”
Section: Discussionmentioning
confidence: 85%